ANALISIS KETAHANAN PANGAN BERBASIS AGROINDUSTRI DENGAN INTEGRASI ASPEK TEKNIS, EKONOMI, DAN KOMUNIKASI MASYARAKAT - Dea Ratna Putri Wibowo; Isna Kumala Sari; Hasbi Ashshiddiqi Wijaya Kusuma (Institute of Computer Science (IOCS), 2026)
Food security is a strategic and multidimensional issue that includes social, economic and environmental aspects. The global context explains that food security sustainability is a priority agenda for various countries and international institutions. Along with the increase in population growth, climate change and limited natural resources to the instability of food supply. Although various studies examine food security from production, economic, and social perspectives, this study integrates technical aspects, economic aspects, and community communication in one agroindustrial-based research. Food security is the result of various factors that affect each other upstream to downstream. Based on the background above, the purpose of the research is to analyze the influence of technical aspects, economic aspects, and community communication on agroindustrial-based food security in the upstream to downstream processing of agricultural products. The research results explain that between technical aspects, business or economic feasibility aspects and community communication affect agroindustry-based food security in the upstream to downstream processing of agricultural products. The economic aspect plays an important role from the research results showing the highest coefficient value of 0.38 among other variables so that the economic aspect has an impact in ensuring the sustainability of the food system. The most realistic food procurement policy is through local food production. Local food is one of the solutions to overcome the problem of food security because it is able to meet the aspects of food security elements, namely production, local food system, and food quality.